PERANCANGAN PROYEK ARSITEKTUR KAFE DENGAN PENDALAMAN DESIGN AND BEHAVIOR OLEH KONSULTAN ARSITEKTUR INTERIOR ALUNA STUDIO - Junaedya, Andy Lunarto; Susan, Susan (Universitas Ciputra Surabaya, 2023)
Blitar City is a small city in East Java Province. Blitar itself is a city that was established in 1906. Building a cafe with deeper design and behavior has been implemented into practice in Blitar City to provide a form of building design that originates from the voices of the people of Blitar City. In this project, Aluna Studio Interior Architecture Consultant adopts a holistic approach that integrates interior design with a deep understanding of how human behavior interacts with the spatial environment. The comprehensive study aims to identify the human behavior patterns of those utilizing this cafe from the employees who manage the establishment to the actual cafe customers. This is quite important to determine space placement and the correlation between space and comfort in using this cafe. This was studied using several methods, namely by direct interviews and randomly distributing surveys to the community in Blitar City. With the results of surveys and interviews collected, a classification is made of the desires of various respondents and the considerations of various other respondents. All this resulted in a limitation or special request from several respondents who had participated in taking this survey. The outcomes of this classification are also integrated with regulations for construction and principles of architecture, so that by using these guidelines and classifications we can produce optimal designs in terms of architecture and space arrangement that are comfortable and by the wishes of the community and the clients themselves.